Impaired Visuospatial Transformation but Intact Sequence Processing in Parkinson Disease - Stephen Johnston (Cognitive And Behavioral Neurology, 2014)
Objective: We examined whether visuospatial deficits in Parkinson disease (PD) can be explained by a domain-general, nonspatial impairment in the sequencing or serial chaining of mental operations.Background: PD has been shown to be associated with impaired visuospatial processing, but the mechanisms of this impairment remain unclear.Methods: Thirteen patients with PD and 20 age-matched, neurologically normal controls performed a visuospatial grid navigation task requiring sequential spatial transformations. The participants also performed a control task of serial number subtraction designed to assess their nonvisuospatial sequencing. The tasks were matched in structure and difficulty.Results: The patients were impaired on the visuospatial task but not in serial number subtraction. This finding suggests that visuospatial processing impairments in PD do not derive from a general impairment affecting sequencing or serial chaining.Conclusions: We argue that visuospatial deficits in PD result from impairments to spatial transformation routines involved in the computation of mappings between spatial locations. These routines are mediated by dopaminergic pathways linking the basal ganglia, prefrontal cortex, supplementary motor area, and parietal cortex.